DIAGNOSIS KESULITAN MAHASISWA DI UNIVERSITAS KUNINGAN DALAM PEMBUKTIAN MENGGUNAKAN INDUKSI MATEMATIKA BESERTA UPAYA MENGATASINYA MENGGUNAKAN SCAFFOLDING - Azin Taufik (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2016)
This study was conducted to describe the difficulties of students in the proof using mathematical induction as well as efforts to resolve it using the Scaffolding. Scaffolding is providing assistance given by teachers or peers who are more capable to students so that they can reach their potential level. This study uses a qualitative research design types of case studies, where data is obtained in the form of observations sheet test and an interview with the subject. The subject is based on the results of diagnostic tests that are classified according to type of error is then taken of each group of students as subjects. Based on the research, found the location of the difficulties experienced by students in the proof of proposition using mathematical induction, namely the difficulty in manipulating algebra to show the truth of Pk + 1. Of these difficulties, students are given the scaffolding in accordance with the difficulties faced by each student. Depth scaffolding scaffolding provided is a second level that is explaining, reviewing and restructuring and third tiers of scaffolding that is developing conceptual thinking. The advice given by researchers is the teacher must give emphasis or affirmation special steps to make assumptions and define a form Pk + 1, the student must master the other concepts that relate to a given problem, so as to make the connection between Pk and Pk +1, and similar studies should be conducted with more depth on other types of problems, such as conjecture. Keywords: Diagnosis difficulty, Mathematical Induction, Scaffolding